Sistemas agroflorestais na recuperação de áreas de preservação permanente - Machado, Fábio José (Universidade Federal de São Carlos, 2012)
This essay aims at evaluating the use of alternative reforestation models in order to recover degraded areas in permanent preservation areas. The potential of effective recovery was analyzed regarding sustainability indicators which were applied according to the principles of the MESMIS tool. Comparing a forest fragment (AT), a handled agroforestry system (SAF), two recovery areas and a pasture area. All of the analyzed places belong to strategic regions considering the biodiversity conservation as well as water resources, as they are located in different environmentally protected zones (APA s), which provide water for the Cantareira System (Sistema Cantareira). The analysis took place in the recommended period for the monitor in the RAD projects, in the first three years in order to evaluate the current situation and also intervene in the maintenance if necessary. The sustainability indicators choice was based on the easy applicability and facts interpretation, which belongs to three groups: man-induced disturbance, composition and ecological function. The maninduced disturbance revealed that there was evidence of disturbance in all the places. In the composition indicators, the forestry fragment (AT) showed the higher value considering the biodiversity index. However the difference was not really significant if compared to the handled SAF. In the implementation of ecological function indicators, the SAF showed the highest rate of tree canopy. So, it was determined that the agroforestry system shows good results considering the diversity when it is handled. In addition to that, it showed big viii potential in recovering degraded areas and in enrichment of forest fragments that can be handled for a longer period than the one estimated by law.
Agroforestry systems in the restoration of permanent preservation areas
Keywords: Reflorestamento; Recuperação ambiental; Agroecossistemas; Reforestation; Environmental restoration; Agroecossystems; CIENCIAS AGRARIAS